Body composition and inflammatory markers in pubertal girls: Comparison between athletes and non-athletic controls - Jürimäe, J.; Vösoberg, K.; Tamm, A.-L.; Maasalu, K.; Remmel, L.; Tillmann, V. (European Journal of Sport Science, 2017)
Various inflammation parameters are increased with childhood obesity, but few comparable data are found in lean growing athletes. This study aims to characterize differences in 12 simultaneously measured inflammatory parameters between pubertal rhythmic gymnasts (RG) and untrained controls (UC), and to examine the relationship between body composition and inflammatory markers. Sixty 10-12-year-old girls were divided into RG (n = 30) and UC (n = 30). Fat mass (FM) and fat free mass (FFM) were measured by dual-energy X-ray absorptiometry. Leptin and 12 inflammatory parameters (interleukin [IL]-2, IL-4, IL-6, IL-8, IL-10, vascular endothelial growth factor, interferon-gamma [IFN-?], tumor necrosis factor-alpha, IL-1a, IL-1ß, monocyte chemotactic protein-1 and epidermal growth factor) were measured from fasting blood samples. No differences were seen in 12 inflammatory markers between studied groups. As expected, leptin (RG: 2.4 ± 1.1; UC: 7.6 ± 4.2 ng ml-1) and FM (RG: 7.3 ± 2.3; UC: 11.8 ± 5.1 kg) were lower (p < .05) in RG compared to UC. In the whole group of lean pubertal girls, 69.0% of the variability in body FM was determined by leptin, and 11.2% of the variability in body FFM was explained by IFN-?. In conclusion, measured 12 inflammatory biomarkers were not different between RG and UC, despite lower leptin and FM in RG. In lean pubertal girls, IFN-? was independently associated with FFM, and leptin with FM.